Takhrij and Syarah Hadith of Chemistry: The Role of Pomegranate Skin Extract on Health - Syahrul Gopar Sidik; Haura Alfiyah Nida; Ira Ryski Wahyuni; Badruzzaman M. Yunus; M Solahudin (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet about the benefits of pomegranate peel from a scientific perspective. This research method is qualitative through the approach of takhrij and syarah hadith with chemical analysis. The results and discussion of this study is that pomegranate peel as a traditional medicine has many benefits for the health of the body's organs as a whole. The conclusion of this research is takhrij and syarah hadith of the Prophet about pomegranate peel by chemical analysis shows pomegranate peel has chemical compounds that are beneficial to health and as a strategy development for the need for treatment and prevention of various diseases.